Сто великих наград: научно-популярная литература / сост. Н. А. Ионина - Ионина Н. А. (100 великих, 2009)
Экземпляры: (20161028) / Инвентарный номер: 545 / Цена: / Сис.шифр: 63.3(0) / Авт.знак: С81 / ББК: 63.221-3